2011
DOI: 10.2214/ajr.10.4193
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Ablation in the Spleen for Treatment of Secondary Hypersplenism: A Preliminary Study

Abstract: MW ablation is a safe and effective technique for the management of hypersplenism in patients with liver cirrhosis. Ablating more than 40% of the splenic parenchyma may yield better long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Transient hemoglobinuria was also reported but was not associated with renal dysfunction. These findings, similar to those reported by Liang et al [4], mirror the experience with MWA in the treatment of solid tumors such as hepatocellular carcinoma and are remarkable for their lack of any major complications, though both studies are limited to a small number of enrollees. Since many MWA cases can be performed under moderate sedation, cost and exposure to anesthesia-related complications are minimized.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Transient hemoglobinuria was also reported but was not associated with renal dysfunction. These findings, similar to those reported by Liang et al [4], mirror the experience with MWA in the treatment of solid tumors such as hepatocellular carcinoma and are remarkable for their lack of any major complications, though both studies are limited to a small number of enrollees. Since many MWA cases can be performed under moderate sedation, cost and exposure to anesthesia-related complications are minimized.…”
supporting
confidence: 87%
“…In one of the key endpoints to this study, Jiang et al [5] reported a statistically significant improvement in white blood cell and platelet counts for up to 2 years, through a mean splenic ablation volume of 47.2 ± 7.0 %, exceeding the threshold of [ 40 % described by Liang et al [4] to achieve sustained long-term platelet recovery, further echoed by Liu et al [6], and close to the 50 % target described by Feng et al [7]. Since percutaneous MWA has a more predictable and consistent ablation volume than RFA and splenic embolization, more precise treatment planning is possible.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Previous studies demonstrated that microwave ablation of the spleen for splenomegaly and hypersplenism had a favorable effect on the peripheral lymphocytes (15). This retrospective study aimed to evaluate the safety and efficacy of hepatectomy combined with microwave ablation of the spleen for HCC and hypersplenism.…”
Section: Introductionmentioning
confidence: 99%